Multidimensional Quantitative Measurement Analysis of Big Data Application Ability based on Mathematical Modeling Path - Wang, Changhui (2022 3rd International Conference on Electronics and Sustainable Communication Systems (ICESC), 2022)
Based on the multi-dimensional quantitative measurement of the application ability of big data modeling ideas based on the mathematical modeling path, this paper briefly explains the importance of the fusion of the two, and deeply analyzes the difficulties faced by the current fusion, and proposes a feasible fusion path. In order to provide suggestions and references for higher mathematics educators. Seven quantitative measures of IPC number, patent grant rate, H index, G index, patent effectiveness, and patent implementation rate. Conduct empirical research on the technological innovation capabilities of Chinese universities. Through SPSS software analysis, it is verified that there is a strong system among the indicators. Sexuality and relevance can objectively quantify the technological innovation capabilities of colleges and universities.